Pengolahan Mie dan Stik Sehat Berbahan Dasar Tomat di Kelompok Tani Sabar Subur dan Bina Karya Kabupaten Bengkulu Utara - Yumiati, Yossie; Andriani, Evi; Yulihartika, Rika Dwi; Fariadi, Herri; Anjaly, Ana (Jurnal Dehasen Untuk Negeri, 2025)
Sawang Lebar Village is one of the villages located in Tanjung Agung Palik District, North Bengkulu, Bengkulu Province. Based on data from the Bengkulu Tengah Regency Agriculture Service in 2023, farmers in Sawang Lebar Village generally grow tomatoes as their daily source of income. The nature of tomatoes is that they rot quickly so that unsold fruit is simply thrown away. The purpose of this community service activity is to form a tomato noodle and healthy stick processing business unit and to increase the skills and knowledge of members of the Sabar Subur and Bina Karya Farmers Group regarding food processing. This tomato noodle and healthy stick processing activity has been carried out for 1 month from preparation to implementation of the activity for the implementation of the activity at the Village Hall in Sawang Lebar Village, Tanjung Agung Palik District, North Bengkulu, Bengkulu Province which was attended by mothers from the Sabar Subur and Bina Karya Farmers Group consisting of 20 (twenty) people. During the activity, there were no obstacles faced because each participant, the day before the activity was carried out, had received material on processing tomato sticks and tomato noodles.